Elderly Educated Blacks and the influence of exercise identity, self-determination, and social determinants of health on physical activity - George Shaw; Miles Irving (Journal of the Georgia Public Health Association, 2022)
ABSTRACT: Background: This study examined the influence of socio-economic status (SES), exercise self-definition, and self-determination variables on physical activity participation among African American retirees. Methods: Both African American men and women, of at least 60 years of age, were surveyed. All participants lived independently. The data collected included demographic, Godin Leisure-Time Physical Activity Questionnaire (LTPA), Exercise Self-Definition Questionnaire (ESD), Behavioral Regulations Exercise Questionnaire-2 (BREQ-2), and Basic Psychological Needs Satisfaction in Exercise Scale (BPNES). The findings and analysis were conducted using data from149 participants. Results: Only gender was a statistically significant predictor of physical activity participation in the study. Based on self-reports, African Americans with moderate to high SES (MH-SES) were well- above the physically “active” threshold as defined by the LTPA. Conclusions: It was observed that physical activity participation decreased as individuals aged while exercise identity plateaued. MH-SES may have a “buffering” effect among older African Americans by suppressing sedentary lifestyle adoption. Hence, race may not be as salient a factor in predicting physical activity participation among African Americans as once thought. Key words: African Americans, Exercise Psychology, Self-determination theory, Exercise Self-Definition